Perinatal management and follow-up in a child with a prenatal diagnosis of OTC deficiency: a case report - Martín-Rivada, Álvaro; Murray Hurtado, Mercedes; Martín-Hernández, Elena (Frontiers in Nutrition, 2024)
Ornithine transcarbamylase deficiency (OTCD) is the most common disorder of the urea cycle and is caused by a mutation of the OTC gene, located on chromosome X. Its prevalence is estimated at 1 in 80,000 to 56,500 births, but this X-chromosomal inheritance results in males being more affected than females. In neonates affected with this disorder, hyperammonemia after birth can lead to neurological and liver damage that can be fatal. We present a child with a prenatal diagnosis based on an older sibling with the same pathology, which led us to adopt an intensive treatment since the delivery. He was admitted in a neonatal unit and treatment with protein restriction, 10% glucose saline serum and glycerol phenylbutyrate was initiated. To date, after 3,5 years of follow up, growth and neurological development have been adequate, biochemical control has been appropriate except for a simple and mild decompensation during the course of a gastroenteritis. This case emphasises the importance of early diagnosis and treatment to avoid potential complications.